Tinjauan Sistematis Tentang Pemahaman Perilaku Pembelian Pengguna Pemasaran Media Sosial Terhadap Tempat Wisata Kuliner di Surabaya - Pangestu, Ferdinand Ryu Putra; Ap Fatsah, Ratu Padma (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This research is a systematic review that aims to understand the social media marketing purchase behavior of culinary attractions in Surabaya. Through a qualitative approach, this study analyzes various literature and previous research results to identify factors that influence consumer decisions, inducing trust in online reviews, visual appeal of promotional content, and perceived quality. The findings show that social media plays a significant role in shaping culinary tourist’s preferences and purchasing decisions, especially through digital interactions and user experience. This study is expected to contribute to the development of more effective digital marketing strategies and support “hidden gem” culinary to be highlighted later in the local culinary tourism sector.